Performance analysis of iterative turbo decoding stopping criteria with quadrature amplitude modulation / Mohamad Yusuf Mat Nasir ... [et al.] - Mohamad Yusuf Mat Nasir, Muhamad Hazwan; Mohamad, Roslina; Kassim, Murizah; Mat Tahir, Nooritawati (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
Iterative turbo decoding stopping criteria are known to be used in early termination of the turbo decoding iteration without sacrificing its performance. However, most of these stopping criteria were tested using low modulation techniques. In this paper, several stopping criteria were tested using higher modulation techniques, such as quadrature amplitude modulation (QAM). The sign-change-ratio (SCR), hard-decision-aided (HDA), and cross-entropy (CE) stopping criteria were simulated with 4-QAM, 8-QAM, and 16-QAM in additive white Gaussian noise. From the simulation results, HDA and SCR are capable of terminating early at various stages of noise while maintaining the bit error rate performance. However, CE fails to terminate early in high-noise channels and only terminates early when the output of the turbo decoder is in a low-noise channel.